2016
DOI: 10.1585/pfr.11.2405061
|View full text |Cite
|
Sign up to set email alerts
|

Design Status of the Structural Components of the Helical Fusion Reactor FFHR-d1

Abstract: FFHR-d1 is a conceptual design of the Large Helical Device-type fusion reactor. Several design optimizations for FFHR-d1 have been conducted under a multipath strategy. The structural design began from a radial build design of the components using a system code analysis and considering a shielding/breeding blanket design. The support structure must be sufficiently rigid to hold a constant geometric position of the radial build components. Additionally, large apertures are required for the maintenance work of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The basic thickness of the coil-support structure was assumed to be 200 mm, which is 250 mm in the d1A. The superconductor used in the c1 was assumed to have a similar structure to that of the d1A [7,8] and the size was reduced to 43.32 mm×43.32 mm. The magnetomotive force (coil current) in each coil and the current density are also shown in table 1.…”
Section: Coil Layout and Support Structurementioning
confidence: 99%
“…The basic thickness of the coil-support structure was assumed to be 200 mm, which is 250 mm in the d1A. The superconductor used in the c1 was assumed to have a similar structure to that of the d1A [7,8] and the size was reduced to 43.32 mm×43.32 mm. The magnetomotive force (coil current) in each coil and the current density are also shown in table 1.…”
Section: Coil Layout and Support Structurementioning
confidence: 99%
“…Alternative challenging options include a liquid metal divertor using a shower of molten tin [9] and a novel divertor location [10,11] (which will be discussed in 2.4). The first of these options is expected to deliver high divertor durability, small amounts of radioactive waste, and high permissible heat loads.…”
Section: Liquid Metal Divertormentioning
confidence: 99%
“…In order to address this, a proposal has been made to relocate the divertor components by partially removing the HC support. The effectiveness of this novel divertor location was evaluated, and it was shown that the irradiation flux could be reduced to 1/5 to 1/10 of the basic option's value [11]. By using this result, it was estimated that the divertor lifetime could be six years.…”
Section: Novel Divertor Location For the Solid Divertormentioning
confidence: 99%